Business and society : corporate strategy, public policy, ethics - Frederick, William C.; Lawrence, Anne T.; Post, James E.; Weber, James (New York : McGraw-Hill, 1996)
This book is about: The corporation in society; The corporation and ethical issues; The corporation in a global society; The corporation and public policy; The corporation and the natural environment; Responding to primary stakeholders; Social issues in management.
Keywords: Business; Society; Social responsibility of business